2015
DOI: 10.1038/bmt.2015.188
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset acute kidney injury is a poor prognostic sign for allogeneic SCT recipients

Abstract: Acute kidney injury (AKI) following stem-cell transplantation (SCT) contributes to a poor prognosis, yet its impact may vary depending on the timing of AKI onset. A prospective cohort study was performed to understand the significance of the onset timing in 103 allogeneic SCT (allo-SCT) recipients. AKI prior to stem-cell engraftment was defined as early AKI and subsequently occurring AKI as late AKI. Propensity score (PS) for early AKI was calculated using a logistic regression model to reduce confounding effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
0
27
1
1
Order By: Relevance
“…Acta Haematol 2020;143:452-464 DOI: 10.1159/000504354 survival (OS) [3][4][5]. Early-onset AKI (within 100 days of transplantation) has been reported to be a particularly unfavorable prognostic factor [6]. Suggested risk factors for AKI following allo-HSCT include septicemia, sinusoidal obstruction syndrome (SOS), thrombotic microangiopathy (TMA), total body irradiation (TBI), and nephrotoxic drugs, such as calcineurin inhibitors (CNIs) and amphotericin B (AMPH-B).…”
Section: Introductionmentioning
confidence: 99%
“…Acta Haematol 2020;143:452-464 DOI: 10.1159/000504354 survival (OS) [3][4][5]. Early-onset AKI (within 100 days of transplantation) has been reported to be a particularly unfavorable prognostic factor [6]. Suggested risk factors for AKI following allo-HSCT include septicemia, sinusoidal obstruction syndrome (SOS), thrombotic microangiopathy (TMA), total body irradiation (TBI), and nephrotoxic drugs, such as calcineurin inhibitors (CNIs) and amphotericin B (AMPH-B).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the avoidance and management of factors associated with mortality are pivotal for improving the survival rates. In allogeneic but not autologous SCT, nephrologists have noted that the development of AKI early after SCT was closely associated with an increased mortality rate in the early phase ( 7 , 8 , 20 , 21 ). Thus, hematologists committed to SCT need to obtain a clearer understanding of current concepts and diagnostic criteria for AKI, monitor changes in laboratory data related to kidney disease, and consult a nephrologist as soon as AKI is suspected.…”
Section: Increasing Number Of Sct Procedures and The Survival Rate Ofmentioning
confidence: 99%
“…Cases of long-term survival are increasing with improvements in transplantation techniques; however, renal disorders that complicate the late stages after transplantation often progress to end-stage renal failure, which may lead to renal replacement therapy 3,4 . Furthermore, renal complications increase morbidity and mortality rates 5 . We recently reported that renal thrombotic microangiopathy (TMA) is associated with chronic graft-versushost disease (GVHD) 6 8 .…”
Section: Introductionmentioning
confidence: 99%